2015
DOI: 10.1038/npjpcrm.2015.32
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of chronic obstructive pulmonary disease (COPD) on diabetes control in diabetes patients: a prospective observational study in general practice

Abstract: Background:Little is known about the association between COPD and diabetes control parameters.Aims:To explore the association between comorbid COPD and longitudinal glycaemic control (HbA1C) and systolic blood pressure (SBP) in a primary care cohort of diabetes patients.Methods:This is a prospective cohort study of type 2 diabetes patients in the Netherlands. In a mixed model analysis, we tested differences in the 5-year longitudinal development of HbA1C and SBP according to COPD comorbidity (present/absent). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
(48 reference statements)
1
7
0
Order By: Relevance
“…In line with this finding, previous studies showed an association between prediabetes and lung function [26,27]. However, progression of lung diseases, such as COPD, may predispose to impairment of glycemic control, though not reported by all studies [28]. Likewise, in a metabolically healthy population, an increase in HbA 1c within the normal range was associated with a decline in pulmonary function [29].…”
Section: Discussionsupporting
confidence: 52%
“…In line with this finding, previous studies showed an association between prediabetes and lung function [26,27]. However, progression of lung diseases, such as COPD, may predispose to impairment of glycemic control, though not reported by all studies [28]. Likewise, in a metabolically healthy population, an increase in HbA 1c within the normal range was associated with a decline in pulmonary function [29].…”
Section: Discussionsupporting
confidence: 52%
“…Other studies already highlighted SES as an important patient characteristic in comorbidity [ 6 ] and in diabetes research [ 16 ] but little has been reported on its role as effect modifier as described here. Further subgroup effect analysis from our own data showed that SES also modifies the effect of long-term SBP control compared between diabetes patients with and without comorbid COPD [ 34 ]. The explorative design of the current study does not allow us to give possible explanations, such as patients’ delay (to visit a doctor) or greater ability for long term risk factor control among specific SES groups.…”
Section: Discussionmentioning
confidence: 99%
“…This paper describes the main results from a larger research project, studying the effects of a number of comorbid diseases on long-term diabetes control parameters. Description of the effects of some specific types of comorbidity on diabetes control parameters in complex interaction models fell beyond the scope of the current paper and will be reported separately [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…This was surprising because previous studies have indicated that the prevalence of DM and COPD comorbidity in patients with high glucose (as indicated by elevated FPG and HbA 1c ) was >10% and that these patients had significantly reduced pulmonary function. 28 , 29 , 30 …”
Section: Discussionmentioning
confidence: 99%